Analysis of the influence of non-pharmaceutical interventions and cultural differences on the evolution of COVID-19 - Duarte, Margarida Martins (2022)
Since the beginning of the COVID-19 pandemic, countries worldwide have implemented a set of Non-Pharmaceutical Interventions (NPIs) as a way to face the evolution of the pandemic. In this dissertation we propose a detailed analysis of the evolution of the pandemic that considers the degree of restriction of NPIs from March 2020 to May 2021 and the reproduction rate in five countries: India, Brazil, United Kingdom, Israel and Portugal. In addition to this, we analyse the impact that Hofstede's cultural dimensions may have between implementations of various degrees of restriction of NPIs and the reproduction rate by applying machine learning models to understand whether cultural characteristics are useful information to improve reproduction rate predictions. To achieve these objectives, we follow the CRISP-DM methodology being that we gather data from Our World in Data COVID-19, Oxford COVID-19 Government Response Tracker and Hofstede Insights website. We show an in-depth and extensive analysis over these months of the pandemic which shows differences between the five countries that have implemented the same NPIs to different degrees and where culture plays an important role in each country's response to the various NPIs implemented.